2019
DOI: 10.3390/ma12020307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitive Properties of Benzyldimethyldodecylammonium Chloride on Microbial Corrosion of 304 Stainless Steel in a Desulfovibrio desulfuricans-Inoculated Medium

Abstract: Biocides are frequently used to control sulfate-reducing bacteria (SRB) in biofouling. The increasing restrictions of environmental regulations and growing safety concerns on the use of biocides result in efforts to minimize the amount of biocide use and develop environmentally friendly biocides. In this study, the antimicrobial activity and corrosion inhibition effect of a low-toxic alternative biocide, benzyldimethyldodecylammonium chloride (BDMDAC), on a 304 stainless steel substrate immersed in a Desulfovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…As shown in Table 2 , energy-dispersive X-ray spectroscopy (EDS) revealed that this substance was mainly composed of Fe, Cr, Ni, O, S, and P. Iron oxide, among other oxides, is a possible source of oxygen. S can be traced to the SRB in the inocula; this may constitute evidence of the formation of FeS in the biofilm [ 5 , 30 ]. The presence of P is related to the sodium phosphate (Na 2 PO 4 ) in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2 , energy-dispersive X-ray spectroscopy (EDS) revealed that this substance was mainly composed of Fe, Cr, Ni, O, S, and P. Iron oxide, among other oxides, is a possible source of oxygen. S can be traced to the SRB in the inocula; this may constitute evidence of the formation of FeS in the biofilm [ 5 , 30 ]. The presence of P is related to the sodium phosphate (Na 2 PO 4 ) in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the antimicrobial properties of BDMDAC in anaerobic conditions against Dulsulfovibrio desulfuricans were investigated. We previously observed that the application of 25 ppm BDMDAC achieved satisfactory results against microbial corrosion by D. desulfuricans [ 30 ]. According to their respective material safety datasheets (Alfa Aesar, Ward Hill, MA, USA), the medial lethal dose (LD 50 ) of BDMDAC indicates it is less toxic than tributyltin (LD 50 of BDMDAC: 400 mg/kg in rats; LD 50 of tributyltin: 132 mg/kg in rats), but the toxicity of BDMDAC continues to call into question its use.…”
Section: Introductionmentioning
confidence: 99%
“…Many different approaches have been attempted to thwart microbial corrosion [ 100 ], to counteract bacterial adhesion [ 101 ] or to confer bactericidal or antibacterial properties to the material surfaces [ 102 , 103 ], while also improving biological responses, such as hemocompatibility [ 101 , 103 ]. Future research will undoubtedly be aimed at optimizing the biological performances of materials, such as SS, by modifying their surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This choice is connected to the fact that this metal is not Microbial induced corrosion (MIC) corresponds to the corrosion process influenced or driven by the presence of microbial biofilms adhered to the metal surface. MIC prevails in diverse industries and sectors where biofilms are formed on surfaces, and leads to degradation and failure of materials such as carbon steel [3][4][5], aluminum alloys [6][7][8], copper and copper alloys [9][10][11], stainless steel [12][13][14] and concrete [15][16][17]. Some microorganisms in biofilms exhibit extreme tolerance to hostile environments such as acidic and alkaline pH, low and higher temperatures, as well as pressure gradients, and as consequence, MIC has been found in power plants [18], oil and gas pipelines [19], public water supply systems [20], sewers [21], marine engineering infrastructure [22], water cooled heat exchangers [12], radioactive disposal facilities [23], medical devices [24], and even in the water recovery system of the International Space Station (ISS) [24,25] and the Chinese space station [26].…”
Section: Introductionmentioning
confidence: 99%